ANALISIS DAN PERAMALAN DAYA DUKUNG LAHAN TANAMAN PANGAN DI KECAMATAN TEMON KABUPATEN KULON PROGO - Hardina, dini; Widodo, Aris Slamet; Widodo, Widodo (JURNAL RISET AGRIBISNIS & PETERNAKAN, 2018)
This research aims to determine the carrying capacity of agricultural land food crops in Temon Sub districts. Data of this research is taken from secondary data obtained from the Central Statistic Agencies and Department of Agriculture. The data analysis is used to make the levels of the land carrying capacity. Based of the research, level of the carrying capacity in Temon Sub district for 10 years in class I. Land carrying capacity value for 10 years in the Temon Sub district amounted to 2,730. This means that the Temon Sub district has been able to perform the self-sufficiency. Base of the forcasting in 2017-2020, it show that Land carrying capacity in Temon Sub district will decreas every years. In 2020, The land carrying capacity of Temon Sub district has predicted in class II. It means that in 2020, Temon Sub district has been able to do self-sufficiency land food crops but has not been able to provide a decent life for the people. Therefore, Temon Sub district should to improved land crops and productivity of rice and reduce the rate of populating growth.Keywords: The Land Carrying Capacity, Forcasting, Temon Sub district